Elemental and Organic Carbon, Ionic and Non ionic components in TSP and PM Particulates of Kathmandu 10 Valley, Nepal - Sharma, R. K.; Bhattarai, B. K.; Sapkota, B. K.; Gewali, M. B.; Kjeldstad, B.; Ito, N. (Journal of the Institute of Engineering, 2016)
Particulate matters of different aerodynamic diameters; TSP, PM10 for 24 hours were collected on quartz 47mm filter paper using Frm OMNITM Ambient Air Sampler from December 2010 to March 2011 and analyzed. The analysis of these sample collected were carried out by gravimetric, X-ray fluorescent and ion-chromatographic methods. TSP value for the observed period lies between 31.3-84.08 μg/m3 while PM10 ranges from 39.5-104.2 μg/m3. Daily carbonaceous aerosols concentration in TSP varied widely between (5.3-18.2 μg/m3) for Organic carbon (OC) and 5.6-10.2 μg/m3 for Elemental carbon (EC). Similarly in PM10 the range was from 4.8-14.1 and 3.9-10.1 μg/m3 respectively. The OC/EC ratio in the particulate matters ranges from 0.9-1.4. OC/EC ratio within 1.1 infers vehicular emission as a major source of carbonaceous aerosols in the valley. Further, among the nonionic components analyzed (K, Ca, Fe, Ti and Pb ) showed highest concentration of Fe as 2.5 μg/m3 while lowest of Pb as 0.001 μg/m3.The ionic components analyzed shows presence of SO4 2- and NH4 + in most of the samples while Cl-, NO3- and Ca2+ are only in few samples. Few samples of soil analyzed shows maximum of 32 elements. Variation in the concentration of ionic nonionic and carbonaceous aerosols is not related with wind pattern and its velocity. Journal of the Institute of Engineering, 2015, 11(1): 79-87